2002
DOI: 10.17660/actahortic.2002.576.47
|View full text |Cite
|
Sign up to set email alerts
|

Post-Harvest Drying Treatment Effects on Amtimalarial Constituents of Artemiasia Annua L.

Abstract: Two field experiments were carried out in cool temperate maritime latitudes in NW Tasmania (41ºS) to assess whether wilting and drying Artemisia annua plants in the field after harvest had any detrimental effects on artemisinin (the source of important antimalarial drugs) or its precursor artemisinic acid. A third field experiment studied the effect of steam distillation of A. annua for its essential oil, prior to oven drying, on artemisinin and artemisinic acid. In the first two experiments whole plants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 9 publications
3
21
2
Order By: Relevance
“…In a similar field study in Tasmania, Australia, whole plants of a Chinese strain of A. annua were dried under full sun for 21 days. Leaf artemisinin concentration in this low-level strain (ca 0.1%) was increased by ca 100% (Laughlin, 2002). It may be important to assess to what extent these results from continental and temperate environments would apply to sub-Saharan Africa and other tropical regions where potential leaf loss and fungal diseases may be more likely due to the hot and humid weather.…”
Section: Harvesting Drying and Commercializationmentioning
confidence: 89%
See 1 more Smart Citation
“…In a similar field study in Tasmania, Australia, whole plants of a Chinese strain of A. annua were dried under full sun for 21 days. Leaf artemisinin concentration in this low-level strain (ca 0.1%) was increased by ca 100% (Laughlin, 2002). It may be important to assess to what extent these results from continental and temperate environments would apply to sub-Saharan Africa and other tropical regions where potential leaf loss and fungal diseases may be more likely due to the hot and humid weather.…”
Section: Harvesting Drying and Commercializationmentioning
confidence: 89%
“…Essential oils are extracted by steam distillation at temperatures which destroy most of the artemisinin in the tissue, as reported by Magalhães (1996) and Laughlin (2002). It is important to note that if artemisinin is extracted in water below the boiling point, up to 75% of the artemisinin will be present in the aqueous extract (J. F. S. Ferreira, unpublished data).…”
Section: Selecting For Other Secondary Metabolitesmentioning
confidence: 90%
“…It has been introduced into experimental cultivation in India (Singh et al 1986), Thailand, Brazil, Australia, Madagascar and in Europe into The Netherlands, Switzerland and France as far north as Finland (Laughlin 2002). Being the world's most severe parasitic infection, malaria causes more than 1 million deaths and 500 million cases annually.…”
Section: Introductionmentioning
confidence: 99%
“…In view of artemisinin production, post-harvest drying of A. annua under sun, shade or dark with ambient temperature increases artemisinin yield (Laughlin 2002). Lead acetate and NaCl promote artemisinin accumulation (Quareshi et al 2005).…”
Section: Abiotic Stress-induced Artemisinin Biosynthesismentioning
confidence: 99%
“…It was also found that an oligosaccharide elicitor derived from Colletotrichum sp. triggers the signal transduction involving rapid Ca 2+ accumulation, plasma membrane NAD(P)H oxidase activation, and ROS release (Wang et al 2001;2002).…”
Section: Calcium Ionmentioning
confidence: 99%